2023
DOI: 10.3389/fpsyg.2022.1019417
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis of the effects of mental fatigue on athletic performance from 2001 to 2021

Abstract: AimsTo explore the research hot topics and main contents in the field of the influence of mental fatigue on athletic performance, and to provide new ideas and directions for future research in this field.MethodsUsing CiteSpace and VOSviewer visualization tool software core collection of Web of Science database to TS = (“mental fatigue” OR “mental exertion” OR “cognitive fatigue” OR “Cognitive exertion” OR “mental exhaustion” OR “mental tiredness”) AND (“athletic performance” OR “technical skill*” OR “Skill*” O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…The WoS list provides extensive information on definitions, coverage notes, and the most significant impact factor score for various journals selected based on the index ( 28 ). It has been widely used in previous bibliometric studies, including sports ( 24 , 25 ). Therefore, the WoS Core Collection (WoS by Clarivate Analytics) database was used in this bibliometric review.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The WoS list provides extensive information on definitions, coverage notes, and the most significant impact factor score for various journals selected based on the index ( 28 ). It has been widely used in previous bibliometric studies, including sports ( 24 , 25 ). Therefore, the WoS Core Collection (WoS by Clarivate Analytics) database was used in this bibliometric review.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of sport, studies can be found related to coaching leadership ( 22 ), sport management ( 23 ), or sport education ( 24 ). However, there are few studies on sport performance ( 25 , 26 ) and only one in swimming ( 27 ). A bibliometric review of race analysis in swimming can provide insights into collaborative networks among researchers, institutions, and countries.…”
Section: Introductionmentioning
confidence: 99%
“…The criteria for non-inclusion in this study are (1) studies that were unrelated to sports, (2) studies not involving professional or elite athletes, (3) studies that did not consider athlete performance and athletes' personality types as variables, (4) studies that were not full text, and (5) studies that were not written in Korean or English. Conversely, the inclusion criteria for this study were either not mentioned in the non-inclusion criteria or explicitly focused on studies deemed suitable for the research.…”
Section: Inclusion/exclusion Criteriamentioning
confidence: 99%
“…Athletic performance (AP) is directly related to athletes' records and prize money, and academia is aware of the importance of their performance [1]. Factors affecting the AP of athletes in modern society include training [2,3], nutrition [4,5], genetics [6,7], and psychology [8][9][10], and numerous sports field studies (for example [11][12][13]) have been conducted on various factors.…”
Section: Introductionmentioning
confidence: 99%
“…The systematic reviews and meta-analysis studies about EEG were highly cited and popular for example Default-mode brain dysfunction in mental disorders [16], deep learning [17], feature extraction [18] and meta-analysis for randomized controlled trials for Nonpharmacological interventions for ADHD [19]. But the bibliometric analysis is new and was limited to the application of EEG indices in human cognitive performance with 143 items [20], Mild Cognitive Impairment (MCI) research with 2310 items [21], mental fatigue on athletic performance with 658 items [22], Quantitative EEG in neuropsychiatric field with 1904 articles [23], neuromarketing with 30 items [24] and 24 items [25], Consumer Neurosciences with 364 items [26], consumer behavior and marketing with 497 items [27] , strategic management studies with 105 items [28] ,Neurorehabilitation with 874 items [29], Neuroarchitecture Assessment with 295 items [30] and Construction [31].…”
Section: Introductionmentioning
confidence: 99%